2020
DOI: 10.3390/ijms21165681
|View full text |Cite
|
Sign up to set email alerts
|

How the AHR Became Important in Intestinal Homeostasis—A Diurnal FICZ/AHR/CYP1A1 Feedback Controls Both Immunity and Immunopathology

Abstract: Ever since the 1970s, when profound immunosuppression caused by exogenous dioxin-like compounds was first observed, the involvement of the aryl hydrocarbon receptor (AHR) in immunomodulation has been the focus of considerable research interest. Today it is established that activation of this receptor by its high-affinity endogenous ligand, 6-formylindolo[3,2-b]carbazole (FICZ), plays important physiological roles in maintaining epithelial barriers. In the gut lumen, the small amounts of FICZ that are produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 140 publications
(237 reference statements)
2
39
0
Order By: Relevance
“…Recently, several studies, including those from our laboratory, have shown that AhR plays a vital and important role in maintaining intestinal homeostasis, both when conditions are healthy and when not (58)(59)(60)(61)(62). In the current study, we noted that not only did the gut microbiota alter following DTH induction but also caused further changes in the microbiota in the administration of AhR ligands.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, several studies, including those from our laboratory, have shown that AhR plays a vital and important role in maintaining intestinal homeostasis, both when conditions are healthy and when not (58)(59)(60)(61)(62). In the current study, we noted that not only did the gut microbiota alter following DTH induction but also caused further changes in the microbiota in the administration of AhR ligands.…”
Section: Discussionsupporting
confidence: 52%
“…A principal contender as an endogenous AHR ligand was 6-formylindolo [3,2b] carbazole (FICZ), a photo-oxidation product of tryptophan [ 14 , 15 ]. FICZ fulfills the criteria, exhibiting high-affinity/specificity (similar to 2,3,7,8-tetrachlorodibenzo- p -dioxin, TCDD), high potency with regard to CYP1A1 induction and is detectable in vivo [ 16 , 17 , 18 , 19 ]. Additionally, FICZ activity has been revealed to be transient, by virtue of it being a metabolic substrate for CYP1A1, thus establishing a FICZ/AHR/CYP1A1 autoregulatory loop, consistent with an endogenous ligand [ 20 ].…”
Section: Endogenous Ligand/activatorsmentioning
confidence: 99%
“…However, it has become apparent that this criterion is insufficient to validate AHR ligand status. A number of endogenous AHR activators, including flavonoids, arachidonic acid metabolites and certain tryptophan metabolites have been demonstrated to be metabolized by CYP1A1 [ 16 , 20 , 69 , 70 , 71 ]. Thus, it can be envisioned that, in the context of these CYP1A1-labile AHR activators, any compound that may or may not itself bind AHR but presents as a competitive CYP1A1 substrate or inhibitor, will effectively increase AHR activator bioavailability and manifest as an AHR activator.…”
Section: Cyp1a1 Competitive Substrates/inhibitorsmentioning
confidence: 99%
“…Tryptophan metabolites and especially indoles are derived from the commensal fermentation of dietary tryptophan and function as ligands for the aryl hydrocarbon receptor (AhR), a receptor important in the maintenance of intestinal homeostasis, and loss of these metabolites is associated with the occurrence of inflammatory bowel disease [ 31 , 32 ].…”
Section: Protection From Infections: Interaction Between the Gut Mmentioning
confidence: 99%